2021
DOI: 10.2174/1871530321666210112160724
|View full text |Cite
|
Sign up to set email alerts
|

Association between Proliferative Diabetic Retinopathy and Serum Bile Acid Level in Patients with Type 2 Diabetes Mellitus

Abstract: Background: Diabetic retinopathy (DR) is one of the diabetic microvascular complications, which is also one of the important causes of blindness in adults. Objective: To investigate the association between proliferative retinopathy and serum bile acid level in patients with type 2 diabetes mellitus (T2DM). Methods: Three hundred and thirty-six patients with T2DM were included, of which, 229 had a history of more than 10 years without diabetic retinopathy (no diabetic retinopathy, NDR) and 107 had prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on the above 3.2 parts, we have learned that the GM flora and its metabolites were disturbed in the DM/DR. A logistic regression analysis suggests that BAs might function protectively, inhibiting the progression of T2DM into DR ( Su et al, 2021 ). Consequently, BAs present a potential therapy target for retinal diseases.…”
Section: The Potential Treatment For Dr: Regulation Of the Gut Microe...mentioning
confidence: 99%
“…Based on the above 3.2 parts, we have learned that the GM flora and its metabolites were disturbed in the DM/DR. A logistic regression analysis suggests that BAs might function protectively, inhibiting the progression of T2DM into DR ( Su et al, 2021 ). Consequently, BAs present a potential therapy target for retinal diseases.…”
Section: The Potential Treatment For Dr: Regulation Of the Gut Microe...mentioning
confidence: 99%
“…[17][18][19] Su et al found significant differences in serum total BAs between DR and NDR. 20 However, the variation in BA composition and its role in human DR remains unclear.…”
Section: Introductionmentioning
confidence: 99%